EFFECTIVENESS ANALYSIS OF “SHANGRI-LA ACADEMY PROGRAM” TOWARDS EMPLOYEES’ WORKING MOTIVATION AT SHANGRI-LA HOTEL SURABAYA - Lina Fandianto; Eddy M. Sutanto (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
This research has taken place at Shangri-La Hotel Surabaya, an international management hotel. The population of research is 573 respondents. The purpose of this research is to understand the effectiveness of Shangri-La Academy Program and the employees’ working motivation at Shangri-La Hotel Surabaya. The analysis technique uses descriptive quantitative analysis. The result of research showed that there is a dependency between Shangri-La Academy Program and employees’ working motivation Shangri-La Hotel Surabaya.Keywords: employee’s working motivation, Shangri-La Academy Program